PEMBERDAYAAN PEKERJA DALAM PENCEGAHAN HIV/AIDS MELALUI KAMPANYE KESEHATAN DAN SKRINING DINI DI PT X KOTA BATAM - Sari, Chinta Yolanda; Parisma, Wan Intan; Jarti, Nanda; Irawati, Ice; Oktarizal, Hengky; Jading, Rasmin Nur (PUAN INDONESIA, 2025)
HIV/AIDS remains a major public health issue, especially among productive-age workers. In Indonesia, over 51% of new HIV cases in 2023 were reported among workers, highlighting the urgent need for workplace-based interventions. This community service program aimed to empower workers at PT X Batam through health campaigns and early screening for HIV/AIDS. A total of 40 employees were randomly selected to participate in pre-test and post-test assessments involving knowledge and behavioral questionnaires. The intervention included educational leaflets, health campaigns, and HIV/AIDS risk screening. Data were analyzed using the Wilcoxon test. Results showed significant improvements in knowledge and preventive behaviors (p = 0.001). In-depth interviews with company leaders revealed growing institutional commitment to HIV/AIDS prevention. This program demonstrated the effectiveness of targeted workplace health education and screening in improving awareness and reducing stigma. The findings underscore the importance of integrating HIV/AIDS prevention strategies into occupational health policies to foster a healthier and more productive workforce.